2021
DOI: 10.5334/joc.146
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Postural Multitasking Training in Older Adults – Effects of Input-Output Modality Mappings on Cognitive Performance and Postural Control

Abstract: Older adults exhibit impaired cognitive and balance performance, particularly under multi-task conditions, which can be improved through training. Compatibility of modality mappings in cognitive tasks (i.e., match between stimulus modality and anticipated sensory effects of motor responses), modulates physical and cognitive dual-task costs. However, the effects of modality specific training programs have not been evaluated yet. Here, we tested the effects of cognitive-postural multi-tasking training on the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…A number of studies have also shown interference effects during the concurrent performance of motor tasks involving postural control and cognitive tasks, with pronounced effects in the elderly [32,38,39]. The study of Brahms et al [40] investigated the effects of cognitive-motor multi-tasking interventions on postural stability and cognitive performance in healthy older adults. These findings showed that the simultaneous performance of cognitive and postural tasks was moderated by modality compatibility mapping, workload memory, and increased postural demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have also shown interference effects during the concurrent performance of motor tasks involving postural control and cognitive tasks, with pronounced effects in the elderly [32,38,39]. The study of Brahms et al [40] investigated the effects of cognitive-motor multi-tasking interventions on postural stability and cognitive performance in healthy older adults. These findings showed that the simultaneous performance of cognitive and postural tasks was moderated by modality compatibility mapping, workload memory, and increased postural demands.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained data indicate the formation of beneficial effects on cognitive functions in a short time period after CABG, which is especially important in patients to establish medical adherence and optimization of rehabilitation procedures in general. In most previous studies, short-term effects of multi-tasking training were not studied, especially in the cardiac cohort of patients [40,41,43]. It can be assumed that if the duration of the course is extended, it would have a greater positive impact on cognitive performance in cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Effortless cognitive-motor multitasking is an ability that suffers as we are getting older, which could have serious health implications due to an increased risk of fall-related injury in older adults. In the context of cognitive-postural multitasking, the article by Brahms et al (2021) evaluated the effect of a modality-specific, multitasking training intervention in older adults, which utilized the performance benefit of modality compatibility mappings. A six-weeks programme with difficulty progression on both the cognitive and postural tasks compared gains in balance performance between a group that practised with modality compatible task mappings and a group with modality incompatible modality mappings.…”
mentioning
confidence: 99%